ILLUSTRATION IMAGE AS AIK ASSIGNMENT METHOD (AL-ISLAM AND KEMUHAMMADIYAHAN) AND STUDENT UNDERSTANDING OF A CONCEPT - Mir'atun Nisa (Sean Institute, 2023)
Student-centered learning is one effective learning maturity. No except for learning Al-Islam and Muhammadiyah (AIK) courses at Universitas Muhammadiyah Yogyakarta. Religious learning, its concepts, and its meanings are identical to the method of teacher-centered learning. Though, students today include the known Gen Z generation with generation technology with visual and interactive characters so that need exists method learning and methods appropriate assignment with their character for more effective. Method assignment through picture illustration is one alternative for them because with this method the student can be freer creative, imaginative, intuitive, and reflective.